Indian Journal of Nematology: Management of Root-Knot Nematodes, Meloidogyne spp. by Organic Manures in Pomegranate, Punica granatum (Indian Journal of Nematology, 2024)
Root-knot nematodes (RKNs), Meloidogyne spp., are globally important plant parasitic nematodes with broad host ranges, including pomegranate, ‎Punica granatum. In this research, the nematode-suppressing potential of novel organic fertilizers, including undecomposed poultry (UDP) and farm manures (cow manure) (UFM) @ 20 and 40 t/ha, compost @ 40 and 60 t/ha, a biofertilizer Marigold @ 300 g/m2, and a nematicide Cadusafos @ 15 g/m2 was investigated on pomegranate trees in orchards naturally infected with Meloidogyne spp. (M. javanica and M. incognita R2). Numbers of second-stage juveniles (J2) in the soil and numbers of eggs and second-stage juveniles (ESJ2), number of egg masses (EMs), and galls (Gs) were compared before and after soil treatments. UDF 40 t/ha, Marigold, Cadusafos, and UDP 40 and 20 t/ha decreased the number of J2 in the soil by 95.2, 95.9, 90.3, 82.3, and 81.4 per cent, respectively. In the roots, UDP 40 t/ha, Marigold, Cadusafos, UDP 40, and 20t/ha reduced the number of ESJ2 by 95.2, 94.2, 89.6, 77.8, and 72.6 per cent, respectively. In the gall index, UDP 40 t/ha had the highest reduction, 85.32 per cent, followed by Cadusafos at 76.2 and UDP 20 t/ha at 74.2 per cent. In the EM index, the highest reduction was in Marigold (91%), followed by compost 60 and 40 t/ha (65.2 and 51.5%). The growth and productivity of pomegranate trees were also affected by the increase in shoot fresh and dry weight, stem length, leaf size, total number of fruits, and weight of five fruits. It can be concluded that replacing chemical nematicides with organic fertilizers may be considered for the management of RKNs in pomegranate orchards.